The Effectiveness of the Problem-Based Learning Model Assisted by Learning Videos in Improving Science Literacy Skills and Students' Cognitive Learning Outcomes - Masruroh, Masruroh; Joko Siswanto; Joko Sulianto (International Journal of Community Engagement Payungi, 2025)
This study examines the effectiveness of the Problem-Based Learning (PBL) model supported by video learning in improving science literacy skills and students' cognitive learning outcomes. A qualitative approach is used to gain a deep understanding of student's experiences and perceptions during the problem-based learning process with video media. Data collection techniques include in-depth interviews with students and teachers, direct observation during classroom learning, and documentation of learning materials and student discussion results. Data analysis was carried out through the stages of data collection, categorization, and interpretation of findings to reveal the influence of the use of video in PBL on student motivation, engagement, and understanding of science concepts. The results show that the integration of video as a learning medium in the PBL model not only increases students' motivation and active engagement but also enriches a more authentic and interactive learning experience. These findings confirm that the video-assisted PBL model improves students' science literacy skills and cognitive learning outcomes. This study ends with a conclusion that affirms the benefits of using video in PBL and provides practical recommendations for teachers and suggestions for further research in developing learning media and PBL methods.